Satisfaction and usability of the recombinant chorionic gonadotropin prefilled pen: a survey in Italy - Chiara Dallagiovanna; Laura Mensi; Luca Di Gesaro; Irene La Vecchia; Marco Reschini (BioExcel Publishing Ltd, 2022)
Background: Due to high purity, recombinant human chorionic gonadotropin (hCG) is suitable for subcutaneous injection, and hence for self-administration, in assisted reproduction. To increase usability and reduce the risk of dosing errors, a prefilled pen was produced. We investigated the ease of administration and satisfaction with the product amongst patients and healthcare professionals. Methods: A survey was conducted amongst women with infertility who underwent in vitro fertilization treatments with recombinant hCG to trigger ovulation in various clinics in Italy. Results: A total of 276 Italian women were interviewed. The median score of preference for the prefilled pen in comparison with hCG powder to be reconstituted in the solvent was rated as 9 (range 8-10), and 125 women answered that the prefilled pen had major advantages. Reasons for preference of the prefilled pen were linked to ease of use and safety: avoidance of dosage mistakes and of concern of such, ease of administration, certainty that the drug is correctly taken, safe administration and no anxiety. The procedure for recombinant hCG administration through the prefilled pen was judged as easy by 80% of respondents, with a median score of 9 (range 8-10) for easiness on a 1-10 scale. Out of 276 respondents, 249 (90%) had no problem with the injection. Conclusion: Overall, the respondents reported a favourable perception of the prefilled pen with hCG, which was reported to be easy to use and perceived to prevent dosage mistakes.